Changes in anthropometric and fitness profile of Italian regional academy rugby union players - Alexandru Ungureanu; Luca Beratto; Federico Abate Daga; Gennaro Boccia; Corrado Lupo; Paolo Riccado Brustio (Termedia Publishing House, 2021)
In rugby union, physical characteristics may partially contribute to long-term career progression, especially during adolescence. Therefore, the primary purpose of the study was to evaluate Italian regional rugby union academy players' (i.e., under-18) anthropometric and physical characteristics during a competitive season. Body mass, height, upper- and lower-body maximal strength, sprint, and high-intensity running ability were assessed in 29 elite players (backs, n = 13, forwards, n = 16). A mixed-design analysis of variance (ANOVA) for repeated measures showed that backs were shorter (ES = 0.59), lighter (ES = 0.94), stronger relative to body mass (bench press; ES = 0.60; deadlift; ES = 0.63; clean ES = 0.63; rowing ES = 0.67), and fitter (shuttle run max; ES = 0.38; shuttle run tot; ES = 0.79) than forwards. However, the forwards achieved greater sprint momentum (initial sprint momentum; ES = 0.97; maximal sprint momentum; ES = 0.98). During the season, players changed in stature, upper-body maximal strength, jumping, and high intensity running (p   0.05). Maximal strength improved in the first part of the season, whereas jumping and sprinting performances increased in the last part of the season. Therefore, these findings highlight the importance of regularly monitoring the physical development in a long-term perspective, even suggesting that physiological adaptations are heterochronic between positional roles.